A strong and ductile Ti-3Al-8V-6Cr-4Mo-4Zr (Beta-C) alloy achieved by introducing trace carbon addition and cold work. (15th March 2020) - Cao, Sheng; Zhou, Xigen; Lim, Chao Voon Samuel; Boyer, Rodney R.; Williams, James C.; Wu, Xinhua
Abstract: The influences of carbon and cold work on microstructure and mechanical property of Ti-3Al-8V-6Cr-4Mo-4Zr (Beta-C) have been investigated. It has been found cold work alone is effective in improving aging response and refining intragranular alpha precipitates through the dislocations introduced, which increases the strength but reduces the ductility. The minor addition of carbon can lead to discontinuous grain boundary alpha layers and the refinement of both beta grains and intragranular alpha, which results in a significant improvement of mechanical properties with now yield strength of ~1505 MPa, ultimate tensile strength of ~1590 MPa, and 11% elongation. Graphical abstract: Image, graphical abstract